Sandro Penna, Within the Sweet Noise of Life (Altre Modernità, 2022)
Sandro Penna, Within the Sweet Noise of Life (Translated by Alexander Booth, Kolkata, Seagull Books, 2021, 96 pp. ISBN 978-085-742-787-8)by Graziano Krätli